Działalność gospodarcza księżnej Anny Jabłonowskiej (1728–1800) - Skodlarski, Janusz (Zeszyty Wiejskie, 2012)
Duchess Anna Jabłonowska is one of the most prominent, albeit less known reformers of the Polish economy in the second half of the 18th century. She won recognition for selfless and practical regional activity in the field of modification of feudal service system. Implementation of her reforms facilitated upgrading of the Polish agriculture. Duchess’s activity was not a lordly whim but it was upright and arduous work aiming at enhancing social-economic life in the vast regions of the declining First Republic.